"esclave né de quiconque l'achète". The multiple histories of economic texts. Issue 6 (2nd November 2022) - van den Berg, Richard
Abstract: Today doing history of economic thought can mean many things. Most fundamentally, they are the different questions, rather than the methods chosen to answer them, that give rise to varying examinations of the products of previous economists. As a classification, four kinds of questions are suggested. The answers to the various questions may sometimes complement and reinforce each other. But if they do not, this should not necessarily be a problem for continued dialogue. All one needs is an acknowledgment that different perspectives are not mutually exclusive.